Mr. and Mrs. J. Acklen and their children, Charlotte and Joe, in front of their log cabin near Dawson, Yukon Territory, ca. 1900. - University of Washington Libraries. Special Collections Division
PH Coll 246.269 Mrs. Acklen was a school teacher. [Meed journal: "The rustic style home of J. Acklen & family near Dawson."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number